2017
DOI: 10.3389/fimmu.2017.00549
|View full text |Cite
|
Sign up to set email alerts
|

ASCT2 (SLC1A5)-Deficient Mice Have Normal B-Cell Development, Proliferation, and Antibody Production

Abstract: SLC1A5 (solute carrier family 1, member 5) is a small neutral amino acid exchanger that is upregulated in rapidly proliferating lymphocytes but also in many primary human cancers. Furthermore, cancer cell lines have been shown to require SLC1A5 for their survival in vitro. One of SLC1A5’s primary substrates is the immunomodulatory amino acid glutamine, which plays an important role in multiple key processes, such as energy supply, macromolecular synthesis, nucleotide biosynthesis, redox homeostasis, and resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…4h ). Glutamine is predominantly transported by system ASC (SLC1A4 and SLC1A5) and system A and N (SLC38A1, SLC38A2, SLC38A5 and SLC38A7) transporters 27 , 28 . Quantitative proteomics data showed that the predominant glutamine transporters in activated NK cells are SLC1A5 and SLC38A2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4h ). Glutamine is predominantly transported by system ASC (SLC1A4 and SLC1A5) and system A and N (SLC38A1, SLC38A2, SLC38A5 and SLC38A7) transporters 27 , 28 . Quantitative proteomics data showed that the predominant glutamine transporters in activated NK cells are SLC1A5 and SLC38A2 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, SLC1A5 knockout mice have been generated (Supplementary Fig. 6c), which show no major phenotype 25 . Interestingly, trans-cervical infection of these mice revealed a significant growth defect of Chlamydia in the absence of SLC1A5 compared to control (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, chlamydial growth was severely affected in genital infections of ASCT2/SLC1A5 knockout mice. This first demonstration of a dominant role of host cell glutamine reprogramming in an in vivo infection at all was surprising since this knockout mouse has no other major phenotype 25 . Gln is channeled into different anabolic and catabolic pathways by glutaminolysis, generating Glu and subsequently α-KG, both of which are essential for infection and replication of several viruses 3136 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that knock down of ASCT2 results in tumor growth attenuation in vitro (Nicklin et al, 2009 ; Wang et al, 2014 , 2015 ; van Geldermalsen et al, 2016 ; Schulte et al, 2018 ) and in vivo (Wang et al, 2015 ; van Geldermalsen et al, 2016 ), and the viability of ASCT2 knockout mice suggests that pharmacological targeting of ASCT2 may not affect normal cells (Nakaya et al, 2014 ; Masle-Farquhar et al, 2017 ). Indeed, a recent study showed that pharmacological inhibition of ASCT2 reduced cancer cell growth and proliferation in vitro and in vivo (Schulte et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%